Moderasi Variabel Penegakan Hukum Berlalu Lintas Terhadap Pengaruh Disiplin Dan Keselamatan Berlalu Lintas Di Kabupaten Pinrang - B, Moh Baktiar; Maryam, St.; Said, Lambang Basri (INTEK: Jurnal Penelitian, 2019)
Abstract—This study aims to analyze the influence of trafficdiscipline and enforcement of traffic law on traffic safety inPinrang Regency and analyze the relationship between lawenforcement moderation and the influence of traffic discipline ontraffic safety in Pinrang Regency. Data collection techniques usedin this study were questionnaires, measurement of variables inthis study using a Likert scale. The data processing in this studyuses the SmartPLS3 Program. Valid data to be sampled are asmany as 100 taken by Slovin techniques, the sample of this studyis the people in Pinrang Regency. Based on the results of thisstudy concluded that traffic discipline and traffic lawenforcement have a positive effect on traffic safety in the districtof Pinrang and law enforcement does not mediate thestrengthening of the influence of traffic discipline on the trafficsafety of road users.